Circular Microfluidic Substrate Integrated Waveguide Resonator Sensor For Materials Characterization - Mohd Bahar, Amyrul Azuan; Zakaria, Zahriladha; Ruslan, Eliyana; Awang Md Isa, Azmi; Al-Ahnomi, Rammah Ali Hussien (Asian Research Publishing Network (ARPN), 2016)
In this paper, a novel planar microfluidic microwave sensor based on a Substrate Integrated Waveguide (SIW) for materials characterization is proposed. The design structure is simulated to analyse the effect of electric flux (electric fields distribution) on the several common liquids. The resonator sensor was integrated with quartz microcapillary which is functioning as sensing tube for characterizing solvents. The SIW resonator sensor is designed at 2 GHz and it demonstrates the changes of resonant frequency as well as the amount of electric flux based on different type of liquid samples. Finally, the operation of the sensor with presence of liquid samples such as water, ethanol, and methanol are performed and reported. This type of microwave sensor is useful for chemical, bio-medical and pharmaceutical applications which are related in materials characterization.